Hydrological Map-Based Modeling of Surface Runoff Volume Using the CNN Model for Wadi Abu Shreish West of Lake Razazza through Geographic Information Systems (GIS) - العبيدي, ازهار سامي خليل (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This study focuses on estimating the surface runoff volume of Wadi Abu Shuraish, located west of Razazah Lake, using the Soil Conservation Service (SCS-CN) method, developed by the U.S. Department of Agriculture. The research relies on analyzing satellite imagery (Landsat 8،sentinel-2) of the study area through remote sensing (IR) techniques and Digital Elevation Models (DEM) to extract hydrological characteristics, land use, soil properties, and climatic data using modern tools such as ArcGIS, WMS, and ERDAS، It was found that the land uses in the study area were (agricultural lands), (natural pastures), and (barren plains), and they occupied an area of​​(5.51,25.90,68.59)%, respectively. As for the group of hydrological soils of the basin, they were within the categories(C,D), and they occupied an area of ​​(3.34, 96.66)%, respectively. The study area, covering the Wadi Abu Shuraish basin, spans 202.23 km². Applying the SCS-CN hypothesis revealed that the total runoff volume reached 1.13 million cubic meters, with a runoff depth (Q) of 5.6 mm, classified as moderate. This runoff holds significant environmental and hydrological importance, particularly during intense rainfall events. Additionally, the peak discharge rate resulting from rainfall in the study area was 314 cubic meters per second for a rainfall intensity of 39 mm/hour. According to international classifications (e.g., USGS-WMO), this falls under the high-intensity category.